Koordinasi Fungsional Antar Instansi dalam Mewujudkan Kota Layak Anak (KLA) di Kota Sukabumi - Lismawati, Salma; Mulyadi, Andi; Meigawati, Dine (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Children are a nation’s strategic asset and have the right to grow and develop in a safe, healthy, and supportive environment. The Indonesian government has issued various regulations, such as Law Number 35 of 2014 on Child Protection and Presidential Regulation Number 25 of 2021 concerning the Child-Friendly City/Regency (KLA) Policy, to ensure the protection and fulfillment of children's rights. Sukabumi City is one of the regions implementing this policy and has achieved the "Madya" (Intermediate) level of KLA recognition. However, the implementation of KLA in Sukabumi still faces numerous challenges, particularly in the cluster of special protection, such as the high number of child abuse cases, limited rehabilitation services, weak inter-agency communication, and low levels of public policy dissemination. This study aims to analyze how functional coordination among government agencies is carried out in efforts to realize a Child-Friendly City in Sukabumi. The research employs a qualitative descriptive method with data collected through in-depth interviews, field observations, and document analysis. The study uses Chandra Bose's coordination theory, which includes six key indicators: clearly defined goals, clear lines of authority and responsibility, comprehensive programs and policies, cooperation, effective communication, and effective leadership and supervision. The findings reveal that coordination has been formalized through the establishment of a KLA Task Force, yet its implementation remains suboptimal due to structural and technical constraints. The study concludes that strengthening functional coordination is essential to enhance the success and sustainability of KLA implementation in Sukabumi City.